TUNGKU GASIFIKASI UNTUK PRODUKSI GAS METAN DARI AMPAS TEBU - S. Rizal; M. Faisal; Erna Yuliwati (LPPM Politeknik Jambi, 2020)
Indonesia is an agrarian country with subtropical climate suitable for planting multicultural and one of those plants is sugar cane. Sugar cane is a raw material for producing sugar, where biomass waste has not been utilized appropriately. The amount of biomass waste was produced of 24-30% from sugar mills. Effective, efficient and environmentally friendly waste treatment technology is needed to utilize the waste into a renewable energy source using gasification methods. Gasification is a process to convert biomass waste to combustible gases (CO, CH4, and H2). This process is combustion with limited air supply (20% -40% stoichiometric air) to break long hydrocarbon chains into short hydrocarbons at high temperatures. This method requires an updraft gasifier furnace that is capable of being operated at high temperatures, which can convert biomass waste into syngas with high conversion. An updraft gasifier is a gasification furnace at temperature of 300-500oC and atmospheric pressure, also used air flow of 10-20 L / min and zeolite as catalyst. This research are devided into few steps, namely drying, crushing, separating, gasification process, The proximate and ultimate method was used to analyze the produced syngas. Proximate analysis is an analysis to measure the calorific value by using a calorimeter bomb, ash content used AAF furnace, and moist water content used a decator. Moreover, ultimate method was used to analyze CH4, H2, O2, N2, CO and CO2 compositions by using Gas Chromatography (GC). Firstly, sugarcane bagasse as the main raw material, were dried and chopped in 7 cm then it were put into the gasifier. The results showed that maximum syngas ratio of combustible gas (CO, H2 and CH4) and noncombustible gas (NGC) of 1.03 with added the zeolit of 200 gr and water of 40 ,L/min.